Patient Satisfaction and Clinical Results at a Mean Eight Years following BHR Arthroplasty: Results from a District General Hospital. Issue 3 (May 2014) - Sandiford, Nemandra A.; Ahmed, Syed; Doctor, Cyrus; East, Debra J.; Miles, Kim; Apthorp, Hugh D.
We present the clinical and radiological results of a prospective study of a consecutive series of patients treated with the Birmingham Hip Resurfacing (BHR) prosthesis between 1999 and 2006 and followed for six to 12 years. Patients were reviewed preoperatively and six, 12, 26 and 52 weeks postoperatively and annually thereafter. They were assessed clinically and radiographically and the Merle d'Aubigne Postel and Oxford Hip scores were calculated at each visit. A SF-36 form assessed general health. Patient satisfaction was assessed by a Visual Analogue Score. Kaplan Meier survival analysis was performed. One hundred and seven patients (109 hips) were included (45 males, 62 females). Median age was 44 years. Mean follow-up was 97.4 months. Median preoperative Merle d'Aubigne Postel and Oxford hip scores were 10 (3-14) and 42 (26-55) respectively. Median SF36 score was 29 (0-65) and patients rated their level of pain as 7.7 on a scale of 0-10 (10 being the worst score). At final follow-up, median MDP and OHS scores were 17 (16-18) and 25 (12-46). Median SF36 score was 72 (27-97). Seven revisions were performed in six females and one male patient. Survival was 96.2% with revision for any reason as the end point. No revisions were performed in the group with hip dysplasia. The BHR prosthesis provides pain relief, high levels of patient satisfaction and improvement of function and well being in the medium-term. Failures occurred primarily in the female group.